Titanium‐Based Nanoarchitectures for Sonodynamic Therapy‐Involved Multimodal Treatments. Issue 12 (15th January 2023) - Maleki, Aziz; Seyedhamzeh, Mohammad; Yuan, Meng; Agarwal, Tarun; Sharifi, Ibrahim; Mohammadi, Abbas; Kelicen‐Uğur, Pelin; Hamidi, Mehrdad; Malaki, Massoud; Al Kheraif, Abdulaziz A.; Cheng, Ziyong; Lin, Jun
Abstract: Sonodynamic therapy (SDT) has considerably revolutionized the healthcare sector as a viable noninvasive therapeutic procedure. It employs a combination of low‐intensity ultrasound and chemical entities, known as a sonosensitizer, to produce cytotoxic reactive oxygen species (ROS) for cancer and antimicrobial therapies. With nanotechnology, several unique nanoplatforms are introduced as a sonosensitizers, including, titanium‐based nanomaterials, thanks to their high biocompatibility, catalytic efficiency, and customizable physicochemical features. Additionally, developing titanium‐based sonosensitizers facilitates the integration of SDT with other treatment modalities (for example, chemotherapy, chemodynamic therapy, photodynamic therapy, photothermal therapy, and immunotherapy), hence increasing overall therapeutic results. This review summarizes the most recent developments in cancer therapy and tissue engineering using titanium nanoplatforms mediated SDT. The synthesis strategies and biosafety aspects of Titanium‐based nanoplatforms for SDT are also discussed. Finally, various challenges and prospects for its further development and potential clinical translation are highlighted. Abstract : Titanium‐based sonsonosensitizers have attracted considerable attention in biomedical sciences especially, in sonodynamic therapy (SDT). This is due to the high biocompatibility, catalytic efficiency, and customizable physicochemical features of the nanostructures. With a focus on the nanoplatforms, this review summarizes the most recent developments in cancer therapy, antibacterial applications, and tissue engineering using titanium‐mediated SDT.